JN.1 COVID-19: Variant of interest - Amalia, Husnun; Mashabi, Yasmine (Fakultas Kedokteran Universitas Trisakti, 2023)
Corona Virus Disease-19 (COVID-19) is an acute respiratory syndrome caused by the Coronavirus 2 (SARS-CoV-2) virus. WHO groups the SARS-CoV-2 virus into two categories, namely a variant of interest (VOI) and a variant of concern (VOC). The VOI category is given if there is a new mutation with predictable phenotypic implications and must be fulfilled by one mutation that causes local transmission or causes multiple clusters or is detected in several countries. In September 2023, a new variant of COVID-19 was detected in the United States, namely JN.1 as VOI. This variant is a variation of the BA.2.86 variant with the only difference being the mutation of 1 spike protein, namely the addition of the L455S protein in the JN.1 variant. This variant has the potential to evade the immune system. Globally, there has been a rapid increase in the number of sufferers, especially in 3 WHO regions, namely America (AMR), West Pacific (WPR) and Europe (EUR). However, the effectiveness of the monovalent vaccine against this variant can still protect sufferers. Several studies show that the risk of hospitalization is low in the case of elderly and young patients.